The Pseudomonas aeruginosa Orphan Quorum Sensing Signal Receptor QscR Regulates Global Quorum Sensing Gene Expression by Activating a Single Linked Operon - Fengming Ding (American Society for Microbiology, 2018)
ABSTRACT Pseudomonas aeruginosa uses two acyl-homoserine lactone signals and two quorum sensing (QS) transcription factors, LasR and RhlR, to activate dozens of genes. LasR responds to N-3-oxo-dodecanoyl-homoserine lactone (3OC12-HSL) and RhlR to N-butanoyl-homoserine lactone (C4-HSL). There is a third P. aeruginosa acyl-homoserine-lactone-responsive transcription factor, QscR, which acts to dampen or delay activation of genes by LasR and RhlR by an unknown mechanism. To better understand the role of QscR in P. aeruginosa QS, we performed a chromatin immunoprecipitation analysis, which showed this transcription factor bound the promoter of only a single operon of three genes linked to qscR, PA1895 to PA1897. Other genes that appear to be regulated by QscR in transcriptome studies were not direct targets of QscR. Deletion of PA1897 recapitulates the early QS activation phenotype of a QscR-null mutant, and the phenotype of a QscR-null mutant was complemented by PA1895-1897 but not by PA1897 alone. We conclude that QscR acts to modulate quorum sensing through regulation of a single operon, apparently raising the QS threshold of the population and providing a “brake” on QS autoinduction. IMPORTANCE Quorum sensing, a cell-cell communication system, is broadly distributed among bacteria and is commonly used to regulate the production of shared products. An important consequence of quorum sensing is a delay in production of certain products until the population density is high. The bacterium Pseudomonas aeruginosa has a particularly complicated quorum sensing system involving multiple signals and receptors. One of these receptors, QscR, downregulates gene expression, unlike the other receptors in P. aeruginosa. QscR does so by inducing the expression of a single operon whose function provides an element of resistance to a population reaching a quorum. This finding has importance for design of quorum sensing inhibitory strategies and can also inform design of synthetic biological circuits that use quorum sensing receptors to regulate gene expression.